Definition and Management of the Immune Tolerance Phase in Chronic Hepatitis B - Young Mi Hong; Ki Tae Yoon (The Korean Journal of Gastroenterology, 2022)
In the natural course of chronic hepatitis B, the immune tolerance phase is characterized by HBeAg positivity, very high levels of HBV DNA, and persistent normal alanine aminotransferase. The international guideline recommendation for patients in this phase is observation without antiviral treatment because of the low risk of disease progression and the lack of effective antiviral agents. However, recent retrospective studies have shown that progression to hepatic fibrosis and hepatocellular carcinoma may occur in patients who are in the immune tolerance phase. Despite the conceptual definition and clinical diagnostic criteria for this phase, it is difficult to accurately diagnose the true immune tolerance phase. Therefore, we should pay attention to the clinical evaluation and interpretation of the immune tolerance phase and understand the clinical situations in which antiviral treatments should be considered.